Household Allocation of Time and Church Attendance - Azzi, Corry; Ehrenberg, Ronald (Journal of Political Economy, 1975)
This paper presents the first systematic attempt by economists to analyze the determinants of individuals' participation in religious activities. A multiperiod utility-maximizing model of household behavior is developed which includes among its implications the shape of a household's life-cycle religious-participation profile and the division of religious participation between husband and wife. The theory is empirically tested using statewide church-membership data and survey data on individuals' frequency of church attendance. The paper concludes by discussing several extensions of the model which lead to additional potentially testable hypotheses.